Evaluating Test Results Using Mathcad - A. V. Oderyshev (Цифровая трансформация, 2024)
The issues of testing students in the process of studying the discipline are considered. The feasibility of such testing is substantiated, procedures for automatic assessment and selection of the students, implemented in the mathematical editor Mathcad, are proposed. All statistical data, given in the examples, was obtained by processing the test results of real study groups. The advantages of such testing are noted, and non-obvious additional possibilities of the procedure provided to the teacher are indicated.